Maximum intervall training: High intensity training for elite performance - Cissik, J.; Dawes, J. (Human Kinetics, 2015)
Are you ready to challenge yourself, and turn up the intensity of your workouts? Are you ready for a proven program that burns fat, increases muscle, and sculpts the physique you`ve always wanted? If so, then Maximum Interval Training is for you!